Patient safety: prescription of drugs that prolong the QT interval - María Jesús Hernández-Arroyo; Alfonso Díaz-Madero; David Menacho-Miguel (Elsevier, 2015)
Objective: to determine the prescription of drugs with known risk to prolong the QT interval in a Healthcare Area, to provide information to those physicians responsible about the risk factors associated with its development, and to improve patient safety. Methods: a descriptive cross-sectional observational study of prevalence. A total of 4, 964 patients from a Healthcare Area treated in one month with drugs with known risk were included in the study. Risk drugs, interactions and predisposing factors were identified. Physicians were provided with the list of patients with drugs with known risk, recommendations, and a questionnaire to know more risk factors, utility and clinical attitude. A descriptive statistical analysis was conducted. Results: of the total number of patients in the Area, 3.2% were treated with drugs with known risk. 64.0% were women, 57.5% were older than 65 years and 39.6% had drug interactions. The mean number of risk factors per patient was 1.78 (CI 95%: 1.74-1.81). Antidepressants (41.2%) and antibiotics (40.4%) were the most commonly prescribed drugs with known risk. 25.4% of the physicians returned the questionnaire and reported the clinical attitude in 1, 073 patients: the drug with known risk was withdrawn in 289, the dose was reduced in 113, and an electrocardiogram was performed in 398. Physicians identified other risk factors: heart disease (17.9%) and hypo/hyperthyroidism (8.8%). Conclusions: the detected prevalence of prescription of drugs that prolong the QT interval is relevant, considering that the patients also had other risk factors. Their identification can improve the quality of care and patient safety.